The genus Cimicicapsus Poppius from China (Hemiptera: Miridae: Deraeocorinae) - Xu, Jing-Yang; Liu, Guo-Qing (Zootaxa, 2009)
Nine species of Cimicicapsus Poppius from China are recognized. Six new species: C. flavimaculus Xu & Liu, sp. n., C. pseudokoreanus Xu & Liu, sp. n., C. rubidus Xu & Liu, sp. n., C. splendus Xu & Liu, sp. n., C. squamus Xu & Liu, sp. n., and C. villosus Xu & Liu, sp. n., are described. A new combination, C. montanus (Hsiao, 1941) and a new synonymy, Deraeocoris luteolus Xu & Liu, 2005= C. parviceps Poppius, 1915, are reported. Photographs of the dorsal habitus and figures of the male genitalia are given. A key to the world species is provided. All type specimens are deposited in the Institute of Entomology, Nankai University, Tianjin, China.